Perception of Code of Ethics on Use of Online Resources for Counselling in National Open University of Nigeria - Okopi, Fidel Onjefu (West African Journal of Open and Flexible Learning, 2015)
With the introduction of online counselling as part of support services in National Open University of Nigeria in March 2014, via the website www.nou.edu.ng/CMS/index.html, it has become imperative to ascertain the Student Counsellors’ perception of code of ethics guiding the use of online resources. Six research questions and six hypotheses were raised based on the 2014 American Counselling Association Code of Ethics section H. Research methodology used for this research included: Descriptive survey of Ex-post facto design and simple random sampling technique which was used to draw a sample of seventy-two out of student counsellors’ population of seventy six. A self-developed Distance Counselling, Technology and Social Media Scale questionnaire (DCTSM) was used for data collection and was pilot tested via Cronbach Alpha correlation, upon which r=0.84 result was obtained. Compared mean scores of the respondents’ perception in the six variables, showed that, the highest mean score of 3.604 obtained in client verification while the lowest mean of .857 was obtained in informed consent. Six hypotheses on gender differences were tested via t-test and the results obtained showed no significant differences between female and male in their responses to all the variables. In conclusion therefore, the NOUN student counsellors have high positive perception of the 2014 ACA Code of Ethics, guiding the use of online counselling resources accepts on informed consent.